Phase structure and piezoelectric properties of Ca- and Ba-doped K 1/2Na1/2NbO3 lead-free ceramics - Taub, Jonathan (2013)
Piezoelectric lead-free ceramics, K1/2Na1/2NbO 3 (KNN) modified with alkaline-earth (AE) Ca2+ and Ba 2+, have been prepared by the conventional solid-state reaction method. The effect of doping level on sinterability and functional response of KNN was studied. In this way, discs doped with 0 to 2 mol% of Ba2+ and Ca2+ were sintered at 1125 °C for 2 h. It was observed that AE changed drastically the microstructure and grain size of KNN when it was added in concentrations higher than 0.5 mol%. Addition of 0.5 mol% of Ba 2+ and Ca2+ produced a softening effect in the ferroelectric properties of the material, while samples prepared with higher contents than 0.5 mol% showed poor properties. © 2012 Elsevier Ltd and Techna Group S.r.l.